Regulatory B Cells in Systemic Sclerosis Isolated or Concomitant With Hashimoto Thyroiditis - Capriello, Silvia; Ferrari, Silvia Martina; Gatto, Ilenia; Santaguida, Maria Giulia; Fallahi, Poupak; Antonelli, Alessandro; Mangino, Giorgio; Romeo, Giovanna; Virili, Camilla; Centanni, Marco (Frontiers in Immunology, 2022)
Systemic sclerosis (SSc) is a systemic autoimmune disease in which gastrointestinal disorders represent a complication in up to 90% of patients. SSc may associate with thyroid autoimmune disorders, with Hashimoto’s thyroiditis (HT) being the more prevalent worldwide. Previous studies have examined the behavior of Th17 lymphocytes and Breg cells in patients with HT and concomitant autoimmune organ-specific disorders. These immune phenotypes seem to play a significant role in the pathogenesis of both these autoimmune processes, but their behavior when these two disorders coexist has not been described. We analyzed Th17 and Breg (CD24hiCD38hi) cell subsets in 50 subjects (45F/5M; median age = 49 years): 18 were healthy donors (HD), 20 had isolated HT, and 12 had SSc, seven of whom had both HT and SSc. Breg cells’ function was also evaluated by measuring their IL-10 production when stimulated by specific activators. An increased percentage of Th17 lymphocytes characterized HT patients as compared to both HD and the whole group of SSc patients (p = 0.0018). On the contrary, the percentage of unstimulated Breg cells in SSc patients was higher (p = 0.0260), either associated or not with HT, as compared to both HT patients and HD, which, instead, showed a similar percentage of Breg cells. Following a specific stimulation with CpG, the percentages of Breg cells were increased in the whole sample of SSc patients (p < 0.001) as well as in isolated SSc and in SSc+HT ones as compared to isolated HT. However, qualitative analysis, obtained through the detection of the IL-10-producing phenotype, revealed that the percentage of CpG-stimulated CD24hiCD38hi-IL10+cells was significantly decreased in SSc patients (p < 0.0001) with no difference between isolated SSc and SSc+HT patients. The IL-10-producing phenotype was instead slightly increased in HT patients as compared to HD (4.1% vs. 2.8%). The presence of SSc seems to be characterized by an enrichment of total Breg cells but by a reduced Breg IL-10-producing phenotype, representing functional Bregs. This last finding was entirely due to the presence of SSc independently from the association with HT. This behavior is different from the ones described about the association of HT with organ-specific autoimmune disorders.